Promoting Sensitive Mother-Infant Interactions in the Neonatal Intensive Care Unit: Development and Design of a Nursing Intervention Using a Theory and Evidence-Based Approach - Lavallée, Andréane; Aita, Marilyn; Côté, José; Bell, Linda; Grou, Bénédicte (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2022)
Introduction: Sensitive mother-infant interactions are important predictors of long-term mother-infant relationship, which is one factor having a positive impact on infant development. Considering preterm infants’ immaturity, mother-infant interactions and maternal sensitivity may not develop optimally. A systematic review showed that current evidence on the effectiveness of parent-infant interventions promoting parental sensitivity in the neonatal intensive care unit (NICU) is of low to very low quality.Objective: The objective of this paper is to report the development process of a novel nursing intervention, using a theory and evidence-based approach, to enhance maternal sensitivity and preterm infant neurodevelopment in the NICU.Methods: The Medical Research Council’s guidance to develop and evaluate complex health interventions, that is an evidence and theory-based approach, was used for this study. Thus, based on the MRC framework, three main steps were conducted: 1- Identifying existing empirical evidence; 2- Identifying and developing theory; 3- Modeling processes and outcomes.Results: We developed a guided participation intervention for mothers to participate in their preterm infant’s care and positioning (‘GP_Posit’). ‘GP_Posit’ is based upon the Attachment theory, the Guided Participation theory as well as the Synactive theory of development.Conclusion: This novel intervention is being tested in a pilot randomized controlled trial (NCT03677752).